Características de la historia de vida de Ariocarpus kotschoubeyanus (CACTACEAE) en el Estado de Querétaro - Arroyo Pérez, Erika (Universidad Autónoma Metropolitana, 2014)
Ariocarpus kotschoubeyanus (Lem.) K. Schum., is a threatened and endemic species of Mexico. Features life story of Ariocarpus kotschoubeyanus are presented from a demographic and reproductive view this work. In the population Barrio Don Lucas, the population density was 0.03 ind/m² , while the density in the study plots was 3.41 ind/m². Individuals have an aggregated spatial distribution and most were found in open spaces. However, individuals who are established under some bush frond, showed a positive asociacon with Karwinskia humboldtiana, showing a preference for the location to the north of this plant. Photosynthetic efficiency and the rate of electron transport indicate that plants are not stressed in open spaces. The structured (N= 305 individuals) hedging sample population and scarcity of seedlings Adults 4. Finite population growth rates λ were 0.91 (± 0.24) and 0.92 (± 0.15) for the first and second year, respectively. The stasis was the most important demographic process and Youth category was the one that had special significance in population dynamics. The population projection of the species over time suggests that this will disappear within 30 years. The life history of A. kotschoubeyanus according to its location in the demographic triangle Silvertown is similar to other globular cactus. Regarding reproductive biology; autumnal flowering and synchronous, flowers have diurnal anthesis, live from one to three days and its main floral visitors were Hymenoptera and your mating system is outcrossing through a xenogamy breeding system. The seeds are positive photoblastic with a germination rate of 64%.; Ariocarpus kotschoubeyanus (Lem.) K. Schum., es una especie amenazada y endémica de México. En este trabajo se presentan las características de Historia de vida de Ariocarpus kotschoubeyanus desde un punto de vista demográfico y reproductivo. En la población Barrio Don Lucas, la densidad poblacional fue de 0.03 ind/m², mientras que la densidad en las parcelas de estudio fue de 3.41 ind/m² . Los individuos presentaron una distribución espacial agregada y la mayoría fueron encontrados en los espacios abiertos. Sin embargo, los individuos que se encuentran establecidos bajo la fronda de algún arbusto, presentaron una asociación positiva con Karwinskia humboldtiana, mostrando una preferencia por la ubicación hacia el Norte de esta planta. La eficiencia fotosintética y la tasa de transporte de electrones indican que las plantas no se encuentran estresadas en espacios abiertos. La población (N=305 individuos) estructurada por coberturas muestra escasez de Plántulas y Adultos 4. Las tasas finitas de crecimiento poblacional λ fueron de 0.91 (± 0.24) y 0.92 (± 0.15) para el primer y segundo año, respectivamente. La permanencia fue el proceso demográfico más importante y la categoría de Juveniles fue la que tuvo especial relevancia en la dinámica poblacional. La proyección de la especie en el tiempo sugiere que esta desaparecerá en menos de 30 años. La Historia de vida de A. kotschoubeyanus de acuerdo a su ubicación en el triángulo demográfico de Silvertown es similar al de otras cactáceas globosas. En cuanto a su biología reproductiva; la floración es otoñal y sincrónica, las flores presentan antesis diurna, viven de uno a tres días y sus principales visitantes florales fueron himenópteros y su sistema de cruza es entrecruza a través de un sistema de apareamiento xenógamo obligado. Las semillas son fotoblásticas positivas con un porcentaje de germinación del 64%.